Perkembangan PDRB Kota Padang Atas Dasar Harga Berlaku Menurut Lapangan Usaha Tahun 2014 – 2018 - Yosi Suryani; Rudy Rinaldy (Politeknik Negeri Padang, 2019)
An area has its own income, usually derived from the transaction process carried out in it. This is called an economic indicator. This economic indicator is used to see the rate of economic growth that has levels from national to regional. At the regional level, such as provinces, districts / cities and even sub-districts, this is known as the Gross Domestic Product (GDP). Because of its role as one of the main indicators in the economy, making this GDP automatically plays an important role. Therefore, the purpose of writing this article is to monitor economic developments that occur in the area, especially in Padang city as the capital of West Sumatra Province. The research method used is a qualitative method by describing the development of Padang City's GDP according to the field of business in 2014-2019 and conducting an analysis within a period of five years. The type of data used is primary data from the Regional Apparatus Organization in Padang and BPS as a source of secondary data. The results of the analysis illustrate that the economic structure of Padang city in 2018 is dominated by 4 sectors as seen from the distribution of the 2018 GDP percentage, namely; Large and Retail Trade, Car and Motorcycle Repair (16.91%), Transportation and Warehousing (16.73%), Manufacturing Industry (13.12%) and Construction (10.38%). These four sectors contributed 57.14% of the total 2018 GRDP which contributed to the 6.09% economic growth in Padang City. The fifth sector is Information and Communication by 6.97%.